PANCASILA VALUES IN ORGANIZING THE COMMUNITY SECURITY AND ORDER BASED ON NEW PUBLIC SERVICE PARADIGM - Johan Bhimo Sukoco, Wulan Kinasih dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Pancasila as Indonesiaâs ideology contains the stateâs idea, norm, and foundation inachieving the objective. Pancasila serves as the basis of state becoming the guideline inevery state organization. It means that every life order in state and nation should build onPancasila values, including the organization of community security and order. Thecommunity security and order (Indonesian: Kamtibmas) is basic service the state shouldprovide to its citizens. On the other hand, public administration science presents a newdevelopment in State organization, particularly in public service. New Public Service is aparadigm in public administration science positioning the citizen to be the subject ofresearch. Denhardt and Denhardt (2007) mentions that there 7 (seven) main ideas in NewPublic Service paradigm: Serve Citizen, Not Customers, Seek the Public Interest, ValueCitizenship over entrepreneurship, Think Strategically, Act Democratically, Recognizedthat Accountability is not Simple, Serve rather than Steer, and Value people, not justproductivity. Some principles or basic ideas in New Public Service ideally become everyapparatusâ reference in providing public service to the public. This research described theapplication of Pancasila values in organizing community security and order based on NewPublic Service Paradigm. This study was a descriptive qualitative research. Techniques ofcollecting data used were interview, observation, and document analysis. Informants wereselected using purposive sampling technique. Data validation was carried out using datatriangulation technique, while data analysis using an interactive model of analysis..Keywords: Pancasila, New Public Service, Community Security and Order